OPTIMIZATION OF PREPARATION METHOD AND CHARACTERIZATION OF TELMISARTAN HYDROCHLORIDE TRIHEMIHYDRATE SALT - Karenina Yuwono, Diandra
Telmisartan is a drug for hypertension therapy in the Angiotensin Receptor Blocker (ARB) class that is categorized as Class II in the Biopharmaceutical Classification System (BCS). Conversion of telmisartan into its salt form using hydrochloric acid (HCl) has been proven to increase the solubility and intrinsic dissolution rate of telmisartan. This study aims to optimize the existing salt conversion to determine the parameters that influence the manufacture of telmisartan hydrochloride trihemihydrate (TEL-HCl.3,5H2O) salt. The parameters altered include crystallization temperature, crystallization surface area, crystallization time, and the amount of ethanol used. The chosen method was selected based on the amount of crystal obtained, shape, and lack of impurities. The crystals obtained were characterized using a polarized microscope, Thermogravimetry-Differential Thermal Analysis (TG-DTA), Powder X-ray Diffractometer (PXRD), and Scanning Electron Microscope (SEM). The crystals were also evaluated by a solubility test, an intrinsic dissolution rate test, and a stability of relative humidity test. The optimum TEL-HCl.3,5H2O were crystals made in an Erlenmeyer flask with 16 mL of ethanol, a crystallization time of 96 hours, a crystallization surface area of 85 mm, and a crystallization temperature of 2-5 O C. There was an increase in solubility of 14.2x and a 4.5x increase in intrinsic dissolution rate when compared with telmisartan. The selected TEL- HCl.3,5H2O have a critical relative humidity of not less than 10% and not more than 83%